2020
DOI: 10.1002/cam4.3409
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between the effects of elective nodal irradiation and involved‐field irradiation on long‐term survival in thoracic esophageal squamous cell carcinoma patients: A prospective, multicenter, randomized, controlled study in China

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 19 publications
0
24
0
Order By: Relevance
“…Several retrospective and prospective studies have found that the main failure mode after IFI is still in-field recurrence and distant metastasis, rather than isolated out-of-field nodal recurrence only ( 30 ). ENI only improves local control but does not improve the long-term survival of patients with EC, and the efficacy of IFI and ENI is essentially similar ( 31 , 32 ). For ENI irradiation mode, the target area volume is not conducive to the protection of peripheral circulating lymphocytes because it covers many large blood vessels and lymphatic tissues in the cervicothoracic region.…”
Section: Discussionmentioning
confidence: 99%
“…Several retrospective and prospective studies have found that the main failure mode after IFI is still in-field recurrence and distant metastasis, rather than isolated out-of-field nodal recurrence only ( 30 ). ENI only improves local control but does not improve the long-term survival of patients with EC, and the efficacy of IFI and ENI is essentially similar ( 31 , 32 ). For ENI irradiation mode, the target area volume is not conducive to the protection of peripheral circulating lymphocytes because it covers many large blood vessels and lymphatic tissues in the cervicothoracic region.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study demonstrated that for patients with positive lymph node metastasis, high-risk regions may receive considerable incidental irradiation doses even if ENI was not used [7] , which means that this incidental irradiation may contribute to the control of micro-metastasis. In the aforementioned studies, only thoracic esophageal cancer patients [4,7,8] or less than 13% of cervical esophageal cancer patients [9,10,12,13] were included. It was unclear that if we should deliver the target of the prophylactic lymphatic area for CESCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Significant decreases were seen in treatment-related esophagitis and pneumonitis with IFI versus ENI. The authors suggest IFI may be superior to ENI in treatment of stage II–III thoracic ESCC due to improved rates of adverse effects, with a similar effect on long-term survival [ 37 ]. In contrast, Xie et al compared CRT with ENI versus CFI in 352 patients with locally advanced ESCC.…”
Section: Radiation Therapy Approachmentioning
confidence: 99%